Analytical Study Of Some Physical And Motor Abilities And Their Relationship With Arm Circle Variables And 25m Arbil League Swimmers’ Achievement - Muhsin, Arif; Hassan, Bahri (Journal of Physical Education, 2018)
Analytical Study Of Some Physical And Motor Abilities And Their Relationship With Arm Circle Variables And 25m Arbil League Swimmers’ Achievement The research aimed at identifying some physical, motor abilities, arm circle, and achievement. In addition to that, the research aimed at identifying the relationship between arm circle variables and 25m swimming achievement of Arbil League swimmers. The researchers hypothesized significant correlations between some physical and motor abilities, arm circle variables as well as 25m swimming achievement. The researchers used the descriptive method. The subjects were Arbil league freestyle swimmers. They used videography of 25m freestyle swimming to measure arm circle. Physical and motor abilities’ tests were conducted including speed, strength, agility and coordination. The data was collected and treated using proper statistical operations. The researchers concluded that there are correlation relationships between physical abilities and some motor abilities (agility and coordination) with all variables of arm circle in 25m freestyle swimming. Keywords: freestyle swimming, arm circle, physical abilities, motor abilities.